Genome Analysis Of Endophytic Escherichia coli USML2 And Its In Planta Ascending Migration With Growth Promoting Effect - Tharek, Munirah (2018)
The discovery of E. coli USML2 from inner leaf tissues of healthy oil palm (Elaeis guineensis Jacq.) raised several questions regarding its presence in planta and benefits to the host plant. Therefore, the ability of E. coli USML2 to migrate from roots into internal leaf tissues of rice seedlings and promote growth of its host plant was investigated. Subsequently, analysis of E. coli USML2 genome was performed to elucidate genes related to in planta ascending migration and plant growth promotion. Finally, importance of in planta migration towards plant growth promotion was also studied. Based on the results, E. coli USML2 colonized the root surface and internal tissues of root, stem and leaf within 24 h of inoculation.